AMC Backed Meta-checkboard Electromagnetic Band Gap Antenna for Pentaband Applications - Kunapareddy Koteswara Rao, Pasumarthy Nageswara Rao, Vangala Sumalatha (International Journal of Advanced Science and Technology, 2020)
A compact S-Shaped antenna is proposed in this work with Artificial Magnetic Conductor (AMC) backing as an Electromagnetic Band Gap structure. A meta surface-based checkboard shaped structure is used in the design of AMC structure to improve the gain of the antenna. Two antenna models are proposed in this work with single split ring resonators and (SRRR) double split rig resonators (DSRR) to achieve the metamaterial behavior in the designed structure. FEM based Electromagnetic simulation tool is used to design, optimize and analyze the antenna model and prototyped model on Jeans substrate is providing excellent measurement correlation with simulation results.